Breaking of Key Layers and Surface Subsidence in the Loess Mountainous Areas. (May 2019) - Lv, Ke; Wang, Jinan
Abstract: During the process of mining subsidence, the thick loess layer will have certain cohesion, tensile strength and flexural strength. Therefore, the thick loess layer may have a significant impact on the overburden load of the mining area, which further affects the fracture and surface subsidence of the overlying strata on the working surface. The calculation model was constructed based on the mining geological conditions of the loess mountainous area in Jinhe Coal Mine of Gansu Province. The mining surface and process were simulated by FLAC 3D, and the load effect of loess layer thickness on its lower strata and its key layers was analyzed. The results show that the surface loess layer is mainly caused by tensile failure, and the other rock layers are mostly shear failure. The key layer has obvious control effect on surface settlement, and its fracture can lead to significant settlement on the surface. Under the condition of thick loess layer, the initial breaking distance of the key layer is larger than that of the critical mining length. The results show that the equivalent load coefficient of the loess layer is obtained and applied to the calculation of the fracture distance, which can obtain more realistic parameters.